Reliability of fire (point) detection system in office buildings in Australia – A fault tree analysis. (July 2020) - MacLeod, John; Tan, Samson; Moinuddin, Khalid
Abstract: The reliability of fire (point) detection systems in office buildings, in Victoria, Australia, was determined through fault tree analysis. Following the literature review and collected data from surveys, a quantitative analysis was undertaken. Fault tree analysis was used as a deductive analysis of the likelihood of the failure of fire (point) detection system in office buildings through mapping the relationship between failure, sub-systems and safety design elements using Boolean logic. The failure probabilities were determined for fifteen components and were compared with data from the literature. This study shows an estimated reliability of fire (point) detection range from 83.17% to 99.74%. This compares well with fire incident data from Tokyo, Japan and Melbourne, Australia. The major components in fire (point) detection system failures are detector heads and detection zone isolation. Recommendations are given to improve the system reliability.